Synthesis of GdB6 nanostructures using nanosecond (Nd: YAG) laser: field emission investigation - Suryawanshi, S. R.; Late, Dattatray J.; More, Mahendra A.; Singh, Anil K.; Sinha, S. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We herein report field emission characteristics of GdB6 nanostructures grown directly on a pellet via laser processing (laser fluence similar to 6 J/cm(2)). The laser processed GdB6 pellet was characterized by X-ray diffraction, which revealed no change in phase upon laser processing. The values of the turn-on field required to draw emission current density of 1 mu A/cm(2) is found to be similar to 2.95 V/mu m, for the laser processed GdB6 emitter. Furthermore, the Fowler-Nordheim (F-N) plot exhibits non-linear behavior over the entire range of applied field and the field enhancement factor (beta) calculated from slope of the F-N plot (low field region) was found to be similar to 543. The emission current stability over a period of 3h was observed to be fairly good. The observed results demonstrate that laser processing can be efficiently used to make GdB6 nanostructure emitter having potential for practical applications.